Pengaruh Pemangkasan Batang dan Cabang Primer terhadap Laju Fotosintesis dan Produksi Jarak Pagar (Jatropha curcas L.) - ,, Hariyadi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
This research was aimed to study the effect of stem and primary branch prunning on photosynthetic rate and production of physic nut. The experiment was conducted in IPB experimental station in Cikabayan, Darmaga, Bogor, from February 2007 until May 2008. A randomized block design with one factor was used in the experiment. The treatments were combination between stem pruning with various height from the soil surface and pruning of primary branches with various number of branch remained. Stem pruning on 40 cm above the soil surface with no branch pruning resulted in the highest photosynthetic rate (8.10 µmol CO2 m-2 s-1), while stem pruning on 20 cm above the soil surface with 2 primary branches remained resulted in the lowest photosynthetic rate (4.71 µmol CO2 m-2 s-1). Stem pruning on 40 cm above the soil surface without branch pruning produced the highest yield components, i.e., capsul number (207.3 capsul plant-1), seed number (506 seeds plant-1) and seed dry weight (323.81 g plant-1). Keywords: photosynthetic rate, production, stem prunning